Upacara Adat Perkawinan Masyarakat Nias Di Kota Padang Tahun 1998-2019 - Siska Stella Monceria Waruwu; Erniwati Erniwati (Jurnal Kronologi, 2021)
The purpose of this research is to see the implementation of the traditional wedding ceremony of the Nias community in Padang City in the midst of the Minangkabau tribe in 1998-2019 and to find out the reasons why there has been a change in the traditional wedding ceremony instruments of the Nias community in Padang City 1998-2019. This study used descriptive qualitative method. Collecting data using interviews, observation, and documentation in order to get accurate results. Data analysis was carried out by collecting data, reducing data, presenting data, and drawing conclusions. The data validity technique used triangulation technique. Based on the results of research conducted on the Nias community in Padang City to be precise in Pondok Village, it was concluded that there was a ceremony left by the Nias community because it was no longer in accordance with the present era and no one could master these procedures, for example there was a death ceremony, there was a molaya or surround the deceased while uttering words of consolation, wailing, ose ose and aju aju, there are things that have not been lost but are rarely held because of the large costs of planning ceremonies such as molau hoasa, private title-enforcing parties, inauguration of traditional shoots because there are no more chiefs and shoot adat, which has the acknowledgment of the head of the customary village in each area of the resident's residence, the cost of jujuran is quite large, of course it has an impact on each individual (can / cannot afford), still uses alcoholic drinks, even though the levels used now are very low, and have even been replaced with fanta drinks and the like, there looks ge nets in the younger generation who are interested in the customs of Nias then each ceremony is determined by those who have a desire. They think that traditional ceremonies are difficult and complicated and require a lot of money, even though it is not the case, and the presence of young men who are married to other ethnicities has resulted in the loss of the man's tribe to his children and the woman who marries another ethnicity where the man and the woman are married. cannot give the tribe to his children. Keywords: Traditional Ceremony, Marriage, Nias